Effect of Blastocyst Morphology and Developmental Rate on Euploidy and Live Birth Rates in Preimplantation Genetic Testing for Aneuploidy Cycles With Single-Embryo Transfer - Li, Na; Guan, Yichun; Ren, Bingnan; Zhang, Yuchao; Du, Yulin; Kong, Hongjiao; Zhang, Yongjie; Lou, Hua (Frontiers in Endocrinology, 2022)
Objective: The aim of this study was to investigate whether blastocyst morphology and developmental rate are associated with euploidy and live birth rates (LBRs) in single euploid frozen–thawed embryo transfer (FET) cycles. Design: Retrospective cohort study. Methods: This study included 431 preimplantation genetic testing for aneuploidy (PGT-A) cycles followed by 393 FET cycles performed at our center from June 2017 to March 2021. All cycles were analyzed for euploidy based on blastocyst morphology (good, average and poor), developmental stage (day 5 and 6) and maternal age (< 35 and ≥ 35 years old). Multivariate logistic analysis models were used to identify the independent effects of blastocyst morphology, developmental rate and morphological parameters (degree of blastocoele expansion, and grade of inner cell mass and trophectoderm (TE)) on LBRs. Results: In the group of women aged < 35 years, compared with poor-quality blastocysts (n = 727), good-quality blastocysts (n = 186) (62.90% vs. 32.46%; OR 3.163, 95% CI 2.247–4.451; P < 0.001) and average-quality blastocysts (n = 394) (46.70% vs. 32.46%; OR 1.665, 95% CI 1.287–2.154; P < 0.001) had significantly higher euploidy. Additionally, day 5 blastocysts (n = 556) were associated with higher euploidy rates than day 6 blastocysts (n = 751) (49.28% vs. 35.02%; OR 1.506, 95% CI 1.191–1.903; P= 0.001). In the group of women aged ≥ 35 years, euploidy rates were also correlated with blastocyst morphology, with 41.86%, 45.65% and 24.39% of good, average and poor-quality embryos, respectively, exhibiting euploidy. However, no correlation was seen between euploidy and blastocyst developmental rate. Multiple logistic regression analysis show that embryos with A-grade TE had significantly higher LBRs than those with C-grade TE (62.71% vs. 45.40%; OR 2.189, 95% CI 1.166–4.109; P=0.015). Similarly, LBRs were significantly higher when day 5 blastocysts were transferred than when day 6 blastocysts were transferred (57.75% vs. 41.67%; OR 2.132, 95% CI 1.370–3.318; P = 0.001). Conclusion: Poor-quality embryos have reduced rates of euploidy. However, blastocyst developmental rate only significantly correlates with euploidy rates in women aged younger than 35. Furthermore, only TE grade and blastocyst developmental rate are significantly associated with LBRs following FET cycles.